Politics of Memory in the City of Ensenada, Buenos Aires, Argentina: the municipal management from 2003 to the present (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this article we develop and explain the Politics of Memory in the City of Ensenada from the year 2003 to the present, under the municipal management of the Mayor Mario Secco. It is during this period that we place a series of initiatives linked to the construction of a social and public memory about the past of State terrorism in the City, carried out by the municipality itself and also by different institutions and actors of the society. In this overview, an attempt will be made to give an account of the social political context that made possible the commissioning and deployment of these actions, and the articulations between the actors involved, that fundamentally claim, commemorate and pay tribute to the disappeared and murdered of this locality.
Keywords: Politics of Memory; Ensenada; State terrorism; Disappeared/Murdered.